How best to palliate and treat emergency conditions in geriatric patients with colorectal cancer. Issue 3 (March 2020) - Zattoni, Davide; Christoforidis, Dimitri
Abstract: Almost one third of colorectal cancer (CRC) cases are diagnosed in an emergency setting, mostly among geriatric patients. Clinical scenarios are often complex and decision making delicate. Besides the obvious need to consider the patient's and/or family and care givers' desires, the surgeon should be able to make the best educated guess on future outcomes in three areas: oncological prognosis, morbidity and mortality risk, and long-term functional loss. Using simple and brief tools for frailty screening reasonable treatment goals with curative or palliative intent can be planned. The most frequent clinical scenarios of CRC in emergency are bowel obstruction and perforation. We propose treatment algorithms based on assessment of the patient's overall reserve and discuss the indications, techniques and impact of a stoma in the geriatric patient. Bridge to surgery strategies may be best adapted to help the frail geriatric patient overcome the acute disease and maybe return to previous state of function. Post-operative morbidity and mortality rates are high in emergency surgery for CRC, but if the geriatric patient survives the post-operative period, oncological prognosis seems to be similar to younger patients. Because the occurrence of complications is the strongest predictor of functional decline and death, post-operative care plays a major role to optimize outcomes. Future studies should further investigate emergency surgery of CRC in the older adults focusing in particular on functional outcomes in order to help physicians counsel patients and families for a tailored treatment.